Analisis Efisiensi Teknis Usaha Penggemukan Sapi Potong di Kabupaten Agam Provinsi Sumatera Barat - I Indrayani; R Nurmalina; A Fariyanti (Universitas Andalas, 2012)
The domestic beef cattle producers have supplied only 70 percent of the national need. Demand of the beef cattle has not been accompanied by an increasing of supply response. One of the major problems in beef cattle farming is its low productivity that might be caused by its low efficiency of input use. Therefore, this study aims are (1) to estimate the factors that influence the production of beef cattle fattening, (2) to analyze the level of technical efficiency of beef cattle fattening. The stochastic production frontier is used to estimate production function. The results showed that quantity of concentrate, dummy of cattle’s age, and dummy of livestock ownership significantly influence production. The average value of the farm technical efficiency is 0.764 ranging from a minimum of 0.478 to a maximum of 0.996.